MANAJEMEN PERBEKALAN KANTOR PALANG MERAH INDONESIA - Utami, Nur Aini Putri; Wagimin, Ign.; Widodo, Jumiyanto (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2012)
Abstract: The purposes of this study were to know the implementation of office supplies management of Rec-Cross (PMI) of Surakarta, the problems, and the solutions to overcome that problems. Used a qualitative approach, the result of research showed that PMI Surakarta implemented the functions of office supplies management to managed their supplies. But, in the practice, got problems with limited human resources and too many functions of warehouse and office management. The efforts to overcome those problems included : empowering the industry apprenticeship?s students and Household employees, coping with over functions by asking for help from other staff and by holding training concerning the instrument use and maintenance, coping with the narrow warehouse and its location in the same room with the office by utilizing the existing vertical room, coping with supply release that was not consistent with the predetermined method by guiding activity accurately and rechecking immediately the stock recording and supply, coping with Staff of Logistic and Inventory division who did not have time to rearrange the warehouse after supply releasing by empowering the industry apprenticeship?s students, coping with virus problem delayed data finding and making report by calling the officers to scan the virus, and coping with roof damage by temporarily solution by putting a rainwater container. Keywords : analysis, supplies management, Red-Cross